Pengaruh Luas Permukaan Telur Terhadap Fertilitas, Daya Tetas, Bobot Tetas dan Mortalitas Ayam Kampung Unggul - Indah Indrawati Bano; Fahria Datau; Dwi Rohmadi; Safriyanto Dako (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2023)
This research was aimedto determine the effect of egg index on fertility, hatchability, hatching weight and mortality of KUB chicken embryos (Kampung Unggul Balitbangtan). This research method used a completely randomized design (CRD) with 3 treatments and 6 replications where each experimental unit consisted of 9 KUB eggs. The three treatments were differentiated based on the egg index value, namely, P1 (72); P2 (72-76) and P3 (76). The results showed that the egg shape index of KUB chickens had no significant effect (P0.05) on fertility, hatchability, hatching weight and embryo mortality.